Real unit labour costs in Eurozone countries: Drivers and clusters - Javier Ordó\~nez; Hector Sala (IZA Journal of European Labor Studies, 2015)
We examine the trajectories of the real unit labour costs (RULCs) in a selection of Eurozone economies. Strong asymmetries in the convergence process of the RULCs and its components-real wages, capital intensity, and technology-are uncovered through decomposition and cluster analyses. In the last three decades, the PIIGS (Portugal, Ireland, Italy, Greece, and Spain) succeeded in reducing their RULCs by more than their northern partners. With the exception of Ireland, however, technological progress was weak; it was through capital intensification that periphery economies gained efficiency and competitiveness. Cluster heterogeneity, and lack of robustness in cluster composition, is a reflection of the difficulties in achieving real convergence and, by extension, nominal convergence. We conclude by outlining technology as the key convergence factor, and call for a wider strategy in labour market policies, which should be more oriented to promote the sources of productivity growth.
Keywords: F43; F62; O47; O52; 330; Real unit labour costs; Eurozone; Real wages; Capital intensity; Technology